Living electronics: A catalogue of engineered living electronic components. Issue 3 (14th December 2022) - Atkinson, Joshua T.; Chavez, Marko S.; Niman, Christina M.; El‐Naggar, Mohamed Y.
Abstract: Biology leverages a range of electrical phenomena to extract and store energy, control molecular reactions and enable multicellular communication. Microbes, in particular, have evolved genetically encoded machinery enabling them to utilize the abundant redox‐active molecules and minerals available on Earth, which in turn drive global‐scale biogeochemical cycles. Recently, the microbial machinery enabling these redox reactions have been leveraged for interfacing cells and biomolecules with electrical circuits for biotechnological applications. Synthetic biology is allowing for the use of these machinery as components of engineered living materials with tuneable electrical properties. Herein, we review the state of such living electronic components including wires, capacitors, transistors, diodes, optoelectronic components, spin filters, sensors, logic processors, bioactuators, information storage media and methods for assembling these components into living electronic circuits. Abstract : Biology leverages a range of electrical phenomena to extract and store energy, control molecular reactions and enable multicellular communication. Recently, the microbial machinery enabling these redox reactions have been leveraged for interfacing cells and biomolecules with electrical circuits for biotechnological applications. Herein, we review the state of such living electronic components including methods for assembling these components into living electronic circuits.